THE VISUAL METAPHOR OF WATER IN FLAT AND SPATIAL MOTION ARTISTRY IN THE CREATION OF ANIMATED FILMS TOYANING MAHAGUNA - Wijaya, I Kadek Adi Putra; Raharja, I Gede Mugi; Suardina, I Nyoman; Pramana, I Made Bayu (Yayasan Education and Social Center, 2026)
Water constitutes a fundamental element of the universe and functions as a primary source of life for all living beings on Earth. In Hindu cosmology, Bhuana Alit (the microcosm of the world) is composed of five essential elements Pertiwi (earth), Apah (water), Teja (fire), Bayu (air), and Akasa (ether) that together structure both the physical environment and human existence. Among these elements, water occupies a particularly vital position, as it is directly perceivable through the human senses and indispensable for biological, social, and spiritual continuity. In Gianyar Regency, especially within the Traditional Village of Tegallalang, natural springs represent not only essential ecological resources but also sacred cultural sites that sustain community life. This research employs a qualitative methodology with an ethnographic approach to examine the animated film Toyaning Maha Guna as a cultural narrative that articulates the significance of water through historical, mythological, and folkloric perspectives. The study integrates observations on water utilization, environmental conditions, and spiritual values embedded in local traditions. Structurally, the film adopts the temporal framework of Tri Semaya Kala, particularly emphasizing Atita (the past) in its opening sequence. This segment portrays the descent of the Trimurti Brahma, Vishnu, and Iswara to rescue the Earth from destruction, symbolizing divine intervention as a response to ecological imbalance. From a Hindu philosophical perspective, the visualization and narrative construct water not merely as a physical resource but as a sacred medium of purification, regeneration, and cosmic harmony. The voluntary descent of the gods signifies an ethical model of responsibility and care toward nature, projecting an ideal relationship between humanity, divinity, and the environment. Through this narrative strategy, Toyaning Maha Guna functions as both an aesthetic expression and an environmental discourse, reinforcing the moral imperative to preserve water sources as the foundation of life, civilization, and spiritual well-being.